Recent Applications of Melanin-like Nanoparticles as Antioxidant Agents - Alexandra Mavridi-Printezi; Arianna Menichetti; Dario Mordini; Riccardo Amorati; Marco Montalti (MDPI AG, 2023)
Nanosized antioxidants are highly advantageous in terms of versatility and pharmacokinetics, with respect to conventional molecular ones. Melanin-like materials, artificial species inspired by natural melanin, combine recognized antioxidant (AOX) activity with a unique versatility of preparation and modification. Due to this versatility and documented biocompatibility, artificial melanin has been incorporated into a variety of nanoparticles (NP) in order to give new platforms for nanomedicine with enhanced AOX activity. In this review article, we first discuss the chemical mechanisms behind the AOX activity of materials in the context of the inhibition of the radical chain reaction responsible for the peroxidation of biomolecules. We also focus briefly on the AOX properties of melanin-like NP, considering the effect of parameters such as size, preparation methods and surface functionalization on them. Then, we consider the most recent and relevant applications of AOX melanin-like NPs that are able to counteract ferroptosis and be involved in the treatment of important diseases that affect, e.g., the cardiovascular and nervous systems, as well as the kidneys, liver and articulations. A specific section will be dedicated to cancer treatment, since the role of melanin in this context is still very debated. Finally, we propose future strategies in AOX development for a better chemical understanding of melanin-like materials. In particular, the composition and structure of these materials are still debated, and they present a high level of variability. Thus, a better understanding of the mechanism behind the interaction of melanin-like nanostructures with different radicals and highly reactive species would be highly advantageous for the design of more effective and specific AOX nano-agents.